2010
DOI: 10.1603/ec08284
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal Activity of Camptothecin Against <I>Nilaparvata lugens</I>, <I>Brevicoryne brassicae</I>, and <I>Chilo suppressalis</I>

Abstract: Greenhouse tests showed that 0.2% camptothecin emulsifiable concentrate (EC) has strong contact toxicity to three agricultural pests, with LC50 and LC90 values of 0.1-0.6 and 0.4-5.0 mg liter(-1), respectively. The descending order of susceptibility was Nilaparvata lugens (Ståhl) > Brevicoryne brassicae (L.) > Chilo suppressalis (Walker). Field tests showed that the corrected mortality of B. brassicae and N. lugens was 94.6 and 69.1%, respectively, which was not significantly different from that with 10% imida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 9 publications
1
26
0
Order By: Relevance
“…5 Experimentally determined LC 50 and LC 90 values of 0.6 and 5.0 µg mL −1 , respectively, indicate that 0.2% camptothecin EC (emulsifiable concentrate) exhibits a strong oral toxic effect against Nilaparvata lugens, Brevicoryne brassicae and Chilo suppressalis. 6 The oral toxic effect of CPT towards S. litura has also been observed in the present authors' laboratory (see supporting information). However, the mechanism of action of CPT as a botanical pesticide is still unknown.…”
Section: Introductionsupporting
confidence: 80%
“…5 Experimentally determined LC 50 and LC 90 values of 0.6 and 5.0 µg mL −1 , respectively, indicate that 0.2% camptothecin EC (emulsifiable concentrate) exhibits a strong oral toxic effect against Nilaparvata lugens, Brevicoryne brassicae and Chilo suppressalis. 6 The oral toxic effect of CPT towards S. litura has also been observed in the present authors' laboratory (see supporting information). However, the mechanism of action of CPT as a botanical pesticide is still unknown.…”
Section: Introductionsupporting
confidence: 80%
“…[105][106][107][108] Additionally, a recent study showed that CPT could cause visible changes in the midguts from the lepidopteran pests Trichoplusia ni and Spodoptera exigua, such as losing the single layer of epithelial cells and disrupting the peritrophicmembrane. 109 Investigations by Zhong et al 110 also demonstrated that CPT-induced apoptosis in SL-1 cells and midgut cells of S. litura. Consistent with these results, Zhang et al 111 recently revealed that CPT caused Sf21 and IOZCAS-Spex-II cell apoptosis via a mitochondrial-dependent apoptosis signal transduction pathway, suggesting that its mode of action may be related to apoptosis.…”
Section: Pesticidal Activitymentioning
confidence: 98%
“…This application rate is economically feasible for practical mite control, based on the current price of ∼ $US 4320 kg −1 CPT as a raw material in China and a low‐cost technology for the production of CPT‐Na + AS with CPT. More importantly, 0.5% CPT‐Na + AS controlled different mite pests as effectively as 0.2% CPT EC controlled different insect pests in a previous study . Compared with the mite control efficacies achieved by aramite, we recommend the median and high rates of the CPT sodium salt for use in mite pest management.…”
Section: Discussionmentioning
confidence: 79%
“…Compared with CPT, first of all, the CPT sodium salt developed in this study is completely soluble in water, forming an aqueous solution that can be easily applied without any other additive and that reduces environmental risk. Previously, the LC 50 values of the formulation 0.2% CPT EC against B. brassicae , N. lugens and C. suppressalis under greenhouse conditions were 0.37, 0.14 and 0.54 mg L −1 respectively, but the time lengths associated with the estimates were not disclosed. In this study, the LC 50 and LT 50 values estimated from the fitted cumulative TCM relationships, incorporating not only the effects of concentration and post‐spray time but also an interaction of both variables, decreased with post‐spray time and sprayed CPT‐Na + concentration respectively.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation